Teachers’ and Students’ Perceptions of Kahoot as an Assessment Tool at a School - Heniki, Reni; Halim, Abdul (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to explore the perceptions of teachers and students regarding the use of Kahoot as an evaluation tool in class VII-B. Employing a quantitative descriptive research design, the study systematically examines the attitudes, opinions, and experiences of participants toward the effectiveness of Kahoot in classroom assessment. Data were collected through structured questionnaires distributed to teachers and students, focusing on their perspectives about the platform’s utility in the evaluation process. The findings reveal that Kahoot is positively perceived by both teachers and students as an effective tool for assessment. Respondents highlighted that the use of Kahoot significantly enhanced student participation and engagement during classroom activities. These results underscore the potential of technology-based assessment tools like Kahoot in fostering interactive and dynamic learning environments. The study offers valuable insights for educators and policymakers on leveraging gamification in educational settings to improve learning outcomes, enhance student motivation, and create more engaging assessment practices.